PENGEMBANGAN SOFTWARE APLIKASI KOMPUTER BERBASIS EXPERT SYSTEM TECHNOLOGY DALAM PEMBELAJARAN AKUNTANSI - Annisa Ratna Sari (Universitas Negeri Yogyakarta, 2006)
PENGEMBANGAN SOFTWARE APLIKASI KOMPUTER BERBASIS EXPERT SYSTEM TECHNOLOGY DALAM PEMBELAJARAN AKUNTANSIThe rapid growth of technology causes a lot of changes in education, teaching process and business sectors. Accounting plays an important role in business activity. To provide competent human resources in educational accounting, it needs instructional innovations using the advance of information and technology. Using Expert System Technology as an accounting educational media is an example for it. Expert system is one subset of Artificial Intelligence which can be used for decision making or problem solving with an expert based knowledge. This article is intended to discuss about Accounting, Modern Learning, Expert System Technology, the Design of Expert System Technology, and the Use of Expert System Technology in Accounting Learning. By reading this article, everyone who related to educational process, is expected to make a quality improvement in accounting learning by using educational technology.